Effect of culture medium nitrogen, phosphorus and potassium on the yield and nutritive value of Lemna gibba L. (Lemnaceae) - Clostre, Gabriel (2006)
Lemna gibba was grown in outdoor to determine the effect of three N-NH4 + :N-NO3 - proportions (1:3, 1:1 and 3:1), as well as the phosphorus (1,5; 3,0 and 4,5 mg.L-1) and potassium (3,0; 6,0 and 9,0 mg.L-1) concentrations added to the culture medium, on the yield and nitrogen, phosphorus and potassium content. Both, fresh and dry weight yields decreased as N-NH4 + proportion increased. Increasing culture medium potassium concentration favored the fresh weight yield. Dry matter content decreased with both N-NH4 + proportions higher than N-NO3 - and increasing the potassium concentration in the culture medium. Nitrogen uptake and content enhanced with high N-NH4 + proportions; and, by increasing phosphorus and potassium concentrations in the culture medium. Phosphorus and potassium uptake and content increased as their respective culture medium concentration increased. High proportions of N-NH4 + in the culture medium decreased phosphorus and potassium content in dry matter. L. gibba yields and crude protein content are optimize with culture medium N-NH4 + :N-NO3 - proportion of 1:1 and 3:1 respectively. Potassium and phosphorus concentrations over 9 and 4,5 mg.L-1 respectively are optimal.